The Influence Of Communication, Leadership Style And Organizational Culture On Job Satisfaction With Work Motivation As Intervening Variables At PT Hki Binjai Project Brandan Zone 2 - Rezza Ardiansyah; M. Isa Indrawan; Mesra B. (Yayasan Multidimensi Kreatif, 2023)
The purpose of this study is to see the influence of communication, leadership style and organizational culture on job satisfaction with work motivation as an intervening variable in PT Hutama Karya Infrastruktur Project Binjai Brandan Zone 2. This research uses a quantitative approach, with statistical methods of path analysis. The population in this study is all contract and permanent employees of PT Hutama Karya Infrastruktur Project Binjai Brandan Zone 2 totaling 86 people. The sampling technique uses saturated samples so that the number of samples is 86 respondents. Partial Least Square (PLS) data analysis technique with Structural Equation Modeling (SEM) equation model. The results showed organizational culture, leadership style, communication, and motivation had no effect on job satisfaction. Leadership style variables have no effect on motivation, while organizational culture and communication affect work motivation. The results of the indirect influence test show that leadership style and organizational culture affect job satisfaction through work motivation as an intervening variable, and communication has no effect on job satisfaction through work motivation as an intervening variable.